2016
DOI: 10.1590/1678-4162-8253
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment improves the performance and behavior of piglets in the nursery phase

Abstract: In modern pig farming, the search for systems that promote environmental quality and welfare is an important issue. In this sense, the present study evaluated the effects of environmental enrichment on the performance and behavior of piglets. In a completely randomized block design, 32 piglets (7.43kg mean weight), weaned at 28 days of age, were distributed into four treatments (control without enrichment, environmental enrichment with wood shavings as bedding; environmental enrichment with hanging toys and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Reduced feed neophobia may result in increased feed intake 10 and consequently better performance post-weaning. It has been shown, for example, that providing hanging ropes and tyres to piglets during several weeks after weaning improved piglet growth and reduced fearful responses towards a person 15 , and providing hanging ropes and wood shavings also improved piglet growth and increased exploration behaviour 16 . Other studies demonstrated that providing peat (for 5 weeks post-weaning) or providing increased space combined with straw, peat and branches (for 2 weeks post-weaning) reduced pig-directed oral manipulation behaviour, and increased exploration behaviour and growth 4 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced feed neophobia may result in increased feed intake 10 and consequently better performance post-weaning. It has been shown, for example, that providing hanging ropes and tyres to piglets during several weeks after weaning improved piglet growth and reduced fearful responses towards a person 15 , and providing hanging ropes and wood shavings also improved piglet growth and increased exploration behaviour 16 . Other studies demonstrated that providing peat (for 5 weeks post-weaning) or providing increased space combined with straw, peat and branches (for 2 weeks post-weaning) reduced pig-directed oral manipulation behaviour, and increased exploration behaviour and growth 4 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…There was higher play behaviour of weaned pigs in the treatment group during the early and late periods. Moreover, the lower proportion of agonistic and belly nosing behaviour had a positive influence on body weight gain of the animals assigned to the toy supplied group (Oliveira et al 2016). In spite of the fact that the rubber toy use in this study has very few traits mentioned in the EU Recommendation, it is still effective for the welfare of weaned pigs.…”
Section: Discussionmentioning
confidence: 63%
“…Especially, environmental enrichment is an obligatory requirement in the EU defined by Directive Animal welfare is one of the most important issues in the modern pig industry (Benson and Rollin 2004). Welfare conditions could be especially important in critical stages, such as weaning of pigs when their performance may be influenced by behavioural, nutritional, and physiological changes (Oliveira et al 2016). Pigs of similar age and body weight are bred in intensive pig production systems (Gracner et al 2013).…”
mentioning
confidence: 99%
“…Beattie et al [34] reported that environmental enrichment reduces time spent inactive and time spent involved in harmful social and aggressive behaviour while increasing the time spent in exploratory behaviour (Table 1). Oliveira et al [35] indicated that environmental enrichment with wood shavings and hanging toys increases the interaction of animals, allowing them to exhibit natural behaviours.…”
Section: Improving Pig Productivity Through Enrichmentmentioning
confidence: 99%